ECTHR_COMMITTEE 63190/16 vom 7. Dezember 2017 , AFFAIRE BECCARINI ET RIDOLFI c. ITALIE - Ecthr Committee (2017)
Violation de l'article 8 - Droit au respect de la vie privée et familiale (Article 8-1 - Respect de la vie familiale); Violation: 8;8-1